Examining childhood experiences and personality functioning as potential predictors for the speed of recovery during psychotherapy of patients with anxiety disorders - Nowak, Jonathan; Nikendei, Christoph; Rollmann, Ivo; Orth, Maximilian; Friederich, Hans-Christoph; Kindermann, David (Frontiers in Psychiatry, 2024)
Background: Adverse childhood experiences were previously identified as relevant risk factors for the development of anxiety disorders. Furthermore, anxiety disorders were shown to be associated with impairments of personality functioning. The objective of this study was to investigate adverse and protective childhood experiences as well as personality functioning, as defined by the Operationalized Psychodynamic Diagnosis system, as potential predictors for the speed of recovery during psychotherapy for patients with anxiety disorders. Method: The sample consisted of n = 312 completed psychotherapies. The speed of recovery, defined as symptom abatement over time, was calculated using a two-stage hierarchical linear model. The effects of adverse and protective childhood experiences as well as personality functioning on the speed of recovery during psychotherapy were then examined using a structural equation model.The presence of adverse childhood experiences predicted a lower speed of recovery during psychotherapy. In addition, a higher number of adverse childhood experiences was associated with greater impairments in the abilities of perception and regulation as dimensions of personality functioning. A higher number of protective childhood experiences was associated with fewer impairments in the communication and attachment dimensions. Impairments in personality functioning in patients with anxiety disorders did not predict the speed of recovery during psychotherapy. Conclusions: Among patients with anxiety disorders, adverse childhood experiences lead to a lower speed of recovery during psychotherapy. Therefore, childhood adversity should be routinely assessed before and thoroughly addressed during psychotherapy in patients with anxiety disorders.